2003
DOI: 10.1084/jem.20021847
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Survival and Homeostatic Proliferation of Natural Killer Cells

Abstract: While the specificity and development of natural killer (NK) cells have been intensely studied, little is known about homeostasis of the mature NK population. Here we show that mouse NK cells undergo homeostatic proliferation when transferred into NK-deficient Rag−/− γC−/− hosts. Normal NK functional activity is maintained during this process, although there are some changes in NK phenotype. Using cell sorting, we demonstrate that mature (Mac-1hi) NK cells undergo homeostatic proliferation in an NK-deficient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
192
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(207 citation statements)
references
References 62 publications
11
192
2
2
Order By: Relevance
“…Analyses of both IL-15-deficient and IL-15 receptor (IL-15R)-deficient mice have demonstrated that this cytokine promotes the differentiation of NK-cell precursors (CD122 + NK1.1 − cells) into immature NK cells (CD122 + NK1.1 + cells), and have additionally suggested that IL-15 also operates at the slightly later stages of NK-cell maturation during which TAM signalling is required [77][78][79][80][81] . It is therefore interesting that a physical and physiological association between the TAM receptor AXL and the α-subunit of the IL-15R has been demonstrated 82 .…”
Section: Tam Control Of Natural-killer-cell Differentiationmentioning
confidence: 99%
“…Analyses of both IL-15-deficient and IL-15 receptor (IL-15R)-deficient mice have demonstrated that this cytokine promotes the differentiation of NK-cell precursors (CD122 + NK1.1 − cells) into immature NK cells (CD122 + NK1.1 + cells), and have additionally suggested that IL-15 also operates at the slightly later stages of NK-cell maturation during which TAM signalling is required [77][78][79][80][81] . It is therefore interesting that a physical and physiological association between the TAM receptor AXL and the α-subunit of the IL-15R has been demonstrated 82 .…”
Section: Tam Control Of Natural-killer-cell Differentiationmentioning
confidence: 99%
“…Although the importance of IL-15 in this process is undisputed [19,20,[22][23][24], it is unclear whether IL-15 1) acts on early NK cell precursors, 2) is only needed at the terminal steps of NK cell development or 3) is important role in maintaining lymphocyte proliferation and homeostasis. To investigate this process, we cultured human umbilical cord blood (UCB) CD34 + Lin − CD38 − primitive progenitors on AFT024.…”
Section: Resultsmentioning
confidence: 99%
“…In human studies, IL-15 is made by stroma and macrophages [21,22]. The importance of IL-15 in the homeostasis of NK [23,24] and T-cells provides further evidence of the physiologic role for this cytokine in the immune system [20]. These studies do not distinguish between the role of IL-15 in homeostatic expansion and survival versus differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…NK cells do not undergo homeostatic proliferation when transferred into NK cell-replete hosts (Prlic et al 2003). In NK cell-deficient hosts, however, adoptively transferred NK cells do proliferate (Prlic et al 2003;Jamieson et al 2004), and the kinetics of their expansion and contraction mirror those of the Ly49H + NK cell subset during MCMV infection (Sun et al 2011).…”
Section: Generating Nk Cell Memory Through Homeostatic Proliferationmentioning
confidence: 99%